Implementasi Program Adiwiyata Sebagai Upaya Penguatan Karakter Dalam Profil Pelajar Pancasila - Anggita, Nifa; utami, ratnasari diah (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2024)
The Adiwiyata program is one of the programs developed by the government through the environment ministry. The Adiwiyata program is one of the programs as an effort to strengthen the character of the Pancasila Student Profile for students. This research aims to describe 1) the implementation of the Adiwiyata Program as an effort to strengthen the character of the Pancasila Student Profile, 2) the attitude of caring for the environment in students in accordance with the Pancasila Student Profile, 3) Obstacles in implementing the Adiwiyata Program. The research method uses descriptive qualitative, data collection is obtained from observation, interviews and documentation. Data analysis uses data reduction, data presentation, and drawing conclusions. Test the validity of the data through triangulation of techniques, sources and time. The results of the research show 1) The implementation of the Adiwiyata Program as strengthening the character of the Pancasila Student Profile at SD Muhammadiyah 1 Ketelan can be implemented through Adiwiyata activities, namely faith and devotion to God Almighty, having noble character through giving thanks and praying before activities, sharing global activities to foster environmental care, mutual cooperation through community service activities, independently disposing of rubbish in its place, critical reasoning in disposing of rubbish according to its type, creatively creating original work, 2) Awareness of the Muhammadiyah 1 Elementary School community regarding the environment in accordance with the character of the Pancasila Student Profile in the implementation of the Adiwiyata Program is already quite high the entire school community actively participates in Adiwiyata activities, 3) The obstacle in implementing Adiwiyata activities at SD Muhammadiyah 1 Ketelan in general is that students are not yet fully able to dispose of waste according to its type.